Feeding bulls-A practical evaluation - D. Simms; L. Corah; Gerry L. Kuhl; R. Schalles (Kansas Agricultural Experiment Station Research Reports, 1984)
Bull calves on nine Kansas ranches were either castrated and implanted with Ralgro, left intact and not implanted, or left intact and implanted with Ralgro, with performance evaluated through slaughter. Bulls produced leaner carcasses and gained slightly faster and more efficiently than steers. However, based on actual prices received, bulls returned 16.09 less to their owners than steers. Implanting with Ralgro during the suckling phase did not influence any of the traits measured. It is evident that marketing is a major problem which makes bull feeding risky
Keywords: Cattlemen& #x27; s Day; 1984; Kansas Agricultural Experiment Station contribution; no. 84-300-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 448; Beef; Bulls; Implants; Performance; Carcass